Jemima’s wrongs: Reading the female body in Mary Wollstonecraft’s prostitute biography - Borham-Puyal, Miriam (International Journal of English Studies, 2019)
A popular eighteenth-century genre, the prostitute’s biography portrayed the lives of harlots for an avid audience. These stories capitalized on the prostitute’s body, exposing its allure and degradation, and directing their censure towards the fallen woman or the cruel society that condemned her. At the same time, they revealed the complex realities of prostitution in the gender, moral and economic politics of their time. In the tradition of the ‘whore biography,’ yet departing from simplistic approaches, Mary Wollstonecraft included the story of a redeemed prostitute, Jemima, as one of the inset narratives of her last work, The Wrongs of Woman (1798). The present article discusses how the prostitute’s story enables Wollstonecraft to expose the control over women’s bodies within an endemically unjust society, regulating their role as mothers, sexual beings and workers, advancing contemporary discussions on women’s function as (re)producers and the ways in which their bodies are still circumscribed.